Location-Dependent DNA Methylation Signatures in a Clonal Invasive Crayfish - Tönges, Sina; Venkatesh, Geetha; Andriantsoa, Ranja; Hanna, Katharina; Gatzmann, Fanny; Raddatz, Günter; Carneiro, Vitor Coutinho; Lyko, Frank (Frontiers in Cell and Developmental Biology, 2021)
DNA methylation is an important epigenetic modification that has been repeatedly implied in organismal adaptation. However, many previous studies that have linked DNA methylation patterns to environmental parameters have been limited by confounding factors, such as cell-type heterogeneity and genetic variation. In this study, we analyzed DNA methylation variation in marbled crayfish, a clonal and invasive freshwater crayfish that is characterized by a largely tissue-invariant methylome and negligible genetic variation. Using a capture-based subgenome bisulfite sequencing approach that covers a small, variably methylated portion of the marbled crayfish genome, we identified specific and highly localized DNA methylation signatures for specimens from geographically and ecologically distinct wild populations. These results were replicated both biologically and technically by re-sampling at different time points and by using independent methodology. Finally, we show specific methylation signatures for laboratory animals and for laboratory animals that were reared at a lower temperature. Our results thus demonstrate the existence of location-dependent DNA methylation signatures in a clonal animal.